Функціонально-технологічний індикатор будівельного проекту - Тугай, О. А.; Сліпенчук, О. В.; Кухта, К. П. (Ways to Improve Construction Efficiency, 2013)
Expounded pre-conditions and theoretical are methodological bases of introduction of complex indicator of estimation of quality of decisions of building project that provides the observance of high standards of quality yet on the stage of investment intention. Due to a synthetic construction, offered index "functionally - the technological indicator of project" provides the simultaneous estimation of both reliability organizationally - technological decisions of building of building objects and readiness of management command by a project and his performers to providing of requirements of customer in the process of preparation of building and building.